(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
Cardiac-specific enzymes, such as creatine kinase MB (CK-MB), troponin I, and troponin T, play a crucial role in assessing the condition of the heart muscle and detecting myocardial damage. Elevated levels of these enzymes in patients with acute surgical pathology may indicate the presence of cardiac complications, which requires special attention and adjustments in the treatment strategy. Preoperative determination of cardiac-specific enzyme levels allows for the assessment of the risk of cardiovascular complications during the perioperative period and enables timely preventive measures to be taken. (1,2)